Evaluation of a self-report distress measure in a high-secure forensic population: CORE-OM psychometric properties and test structure - Gilling, Lindsey (The journal of forensic psychiatry & psychology, 2025)
The Clinical Outcomes in Routine Evaluation Outcome Measure (CORE-OM) is a widely adopted routine patient reported outcome measures across the National Health Service mental health services, including some forensic mental health services. Yet little is known about the measurement properties of the CORE-OM for forensic patients. This study examined the psychometric properties and structure of the CORE-OM in a sample of high-secure forensic patients. T-tests confirmed forensic patients’ scores fall between non-clinical and clinical normative scores. Internal consistency of the overall scale was high, though some score domains demonstrated poor reliability. Principal component analysis revealed a unique three-component structure underlying the CORE-OM items, related to life-functioning and self-worth, relational difficulties, and risk of harm to self. The findings highlight limitations to the generalisability of the original CORE-OM measurement properties to a forensic population. Further research on the CORE-OM is critical given its continued routine use in forensic mental health services.